2014
DOI: 10.11114/jets.v2i2.291
|View full text |Cite
|
Sign up to set email alerts
|

Transactional Distance as a Predictor of Perceived Learner Satisfaction in Distance Learning Courses: A Case Study of Bachelor of Education Arts Program, University of Nairobi, Kenya

Abstract: There is a long history of study and recognition of the critical role of interaction in supporting and even defining distance education. Interaction has been identified as key to the success of distance learning. It is key in fostering, supporting and engaging in the learning process. posits that the physical distance that exists in e-learning courses between the teacher and the students may result in a psychological and communicational gap between them. Such a gap will often impede the ability of the teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 31 publications
5
24
0
3
Order By: Relevance
“…The former is an interesting recommendation given that Moore (1993) does not focus on the frequency of interaction but rather on the quality. Mbwesa (2014) found that learnerteacher transactional distance was experienced by most of the students in her study, and as a result, Mbwesa recommends increased opportunities and frequency of interaction between learners and teacher. One challenge that Mbwesa found facing teachers is that many of them are simply expected to begin teaching distance education courses without any training on how to effectively transfer courses to the digital environment and may therefore be unknowledgeable about how to compensate for the absence of face-to-face interaction.…”
Section: Learner-teacher Interactionmentioning
confidence: 99%
See 4 more Smart Citations
“…The former is an interesting recommendation given that Moore (1993) does not focus on the frequency of interaction but rather on the quality. Mbwesa (2014) found that learnerteacher transactional distance was experienced by most of the students in her study, and as a result, Mbwesa recommends increased opportunities and frequency of interaction between learners and teacher. One challenge that Mbwesa found facing teachers is that many of them are simply expected to begin teaching distance education courses without any training on how to effectively transfer courses to the digital environment and may therefore be unknowledgeable about how to compensate for the absence of face-to-face interaction.…”
Section: Learner-teacher Interactionmentioning
confidence: 99%
“…While both of these studies approached dialogic interactions, they each sought to explore slightly different questions. Mbwesa (2014) studied 168 students studying in the online BA program at the University of Nairobi, Kenya to explore how predictive perceived transactional distance was of student satisfaction, and this research found that the perceived transactional distance of learner-learner, learner-instructor, and learnercontent interactions were predictive of overall student satisfaction. Ekwunife-Orakwue and Teng (2014) found that dialog impacted on student satisfaction but not on student grades.…”
Section: Dialogic Interactionmentioning
confidence: 99%
See 3 more Smart Citations